Implementasi Manajemen Kinerja Sumber Daya Manusia Pada Organisasi/Perusahaan (Studi Pustaka) - Nurul Haliza Siregar; Muhammad Irwan Padli Nasution (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
This research aims to find out how the theory and implementation of performance management to human resources in organizations is discussed using a qualitative method-literature study by collecting data sourced from books, journals and existing research. The results of the study found that performance management functions and is useful as a factor in increasing organizational and company performance which is caused by the alignment of individual and organizational vision-mission goals.